2016
DOI: 10.1097/bpo.0000000000000452
|View full text |Cite
|
Sign up to set email alerts
|

Early Career Experience of Pediatric Orthopaedic Fellows: What to Expect and Need for Their Services

Abstract: Positive messages from this survey include the satisfaction of graduates with their fellowship training, the high percentage of graduates who readily found employment, and the satisfaction of graduates with their current practice environments; this indicates that the pediatric orthopaedic job environment is not completely saturated and there are continued opportunities for graduating pediatric fellows despite the increased number of fellows being trained. Although not determined by this study, it may be that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…27 Clearly, there is a maldistribution of POSNA members. At the 2014 fellowship directors' meeting, 16% of programs indicated that they may add 1 or more fellowship spots in the next 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Clearly, there is a maldistribution of POSNA members. At the 2014 fellowship directors' meeting, 16% of programs indicated that they may add 1 or more fellowship spots in the next 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these regional and national trends, in some areas in the US there may be a relative excess or deficiency of POS. 27 This needs to be followed both from a workforce and outcomes perspectives. In a recent study of POS fellowship graduates, 86% chose employment based on geography and family preferences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is reflected in a trend towards an increased number of fellowships completed that has been identified in the literature, where an estimated 28-30% of physicians are pursuing another fellowship after completing a pediatric orthopaedic fellowship. 3,8 As of 2018, 14.1% of pediatric orthopaedic fellows had completed or planned to complete a second fellowship, with the most common being sports medicine (46%). 3 Depasse et al 1 found that out of the 10 most commonly combined fellowships, the combination of pediatric orthopaedics and sports medicine was the only one that demonstrated a statistically significant rate increase.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 60% (n=33/55) of participants had completed either 2 fellowships or completed a combined pediatric sports fellowship. This is reflected in a trend towards an increased number of fellowships completed that has been identified in the literature, where an estimated 28-30% of physicians are pursuing another fellowship after completing a pediatric orthopaedic fellowship 3,8. As of 2018, 14.1% of pediatric orthopaedic fellows had completed or planned to complete a second fellowship, with the most common being sports medicine (46%) 3.…”
Section: Discussionmentioning
confidence: 99%